(untitled) (Praxis Educativa, 2020)
Functional alphabetization has become a growing need in education in several countries of Latin America. The present investigation details the results obtained from a functional literacy process aimed at parents of a school in Chile. The research base had a foundation focused on the interpretive paradigm, then, it was sought to create a closeness to the realities of the subjects in a holistic and natural way, thus understanding the sensitivity of each proxy from the experience of being literate. A diagnosis was applied to identify the level of learning that each subject had. With these data we proceeded to the elaboration of a didactic proposal, considering the diversity of ages that were in the group and the strategies that should be used to make them more dynamic. The results revealed that after one year the attorneys showed an 80% improvement in their alphabetization level compared to the initial situation. It is concluded that the group of alphabetized parents improved theirself-confidence and became a subject that communicates and shares their life experiences.